Proving the Resonance of DO, RE, MI, FA, SOL, LA, SI, High DO Tones by Comparing Frequency of Sound Produced by Wine Glasses - Ramadhani, Hanifah Asma; Syamra, Fifi Mufida; Melati, Bunga Chinta; Pasaribu, Ibrahim Farisya; Kusumah, Fuji Hernawati (Universitas Islam Negeri (UIN) Mataram, 2024)
Due to the lack of standard laboratory facilities in many schools in Indonesia, the researcher created a simple musical instrument based on the concept of sound physics. The research was to prove the phenomenon of ‘resonance’ with the frequency comparison of the sound from ‘wine glasses’. Eight identical glasses filled with water at different heights to produce the do, re, mi, fa, sol, la, si, and do. The results showed the longer the air column, the higher the frequency of the sound produced. The sound produced by the glasses filled with less water was louder than the glasses filled with more water. This happened because of the resonance between the sound waves produced by the glasses and the sound waves propagating in the tube. Thus, it was following the theory. It could be used in the laboratory. As suggested, the researcher used tall and straight wine glasses to make it easier.